Distribución, abundancia y haÌbitos alimentarios de la nutria (Lontra longicaudis annectens Major, 1897) en el Río Grande, Reserva de la Biosfera TehuacaÌn-CuicatlaÌn Oaxaca, México - Duque-DaÌvila, Diana Laura; Martínez-Ramírez, Emilio; Botello-López, Francisco Javier; Sánchez-Cordero, Víctor (THERYA, 2013)
We report information on the distribution, abundance and food habits of the Neotropical river otter Lontra longicaudis annectens, based on 386 collected scats (281 in the dry season, and 105 in the rainy season). The distribution along a 39.5 km transect was similar in both rainy and dry seasons. The estimates of relative abundance using two models varied according to rates: Gallo-Reynoso (0.508 scats/ km), and Eberhardt-Van Etten, modified for this study (0.016 scats/ km). We obtained a record of L. longicaudis with a collecting effort of 18 nights / camera confirming the presence of the species. Food habits analyzing 161 scats revealed presence of seven species of fish (89.62%) of the families Cichlidae, Heptapteridae and Poeciliidae, four reptiles (4.32%) of the families Corythophanidae, Iguanidae and Phrynosomatidae, an unidentified bird (1.77 %), insects of the family Megaloptera (4.13%), and unidentifiable organic matter (0.17%). We recommend continuing studying the natural history of this species for conservation purposes. Key words: Abundance, distribution, feeding habits, Lontra longicaudis annectens, Neotropical otter, Oaxaca.